Family screening for hypertrophic cardiomyopathy: Is it time to change practice guidelines?. (6th June 2019) - Lafreniere-Roula, Myriam; Bolkier, Yoav; Zahavich, Laura; Mathew, Jacob; George, Kristen; Wilson, Judith; Stephenson, Elizabeth A; Benson, Leland N; Manlhiot, Cedric; Mital, Seema
Abstract: Aims: Current guidelines recommend initiating family screening for hypertrophic cardiomyopathy (HCM) after age 10 or 12 years unless early screening criteria are met. The aim was to evaluate if current screening guidelines miss early onset disease. Methods and results: Children who underwent family screening for HCM before age 18 years were analysed. Major cardiac events (MaCEs) were defined as death, sudden cardiac death (SCD), or need for major cardiac interventions (myectomy, implantable cardioverter-defibrillator insertion, transplantation). Of 524 children screened, 331 were under 10 years of age, 9.9% had echocardiographic evidence of HCM, and 1.1% were symptomatic at first screening. The median (interquartile range) age at HCM onset was 8.9 (4.7–13.4) years, and at MaCE was 10.9 (8.5–14.3) years with a median time to MaCE from HCM onset of 1.5 (0.5–4.1) years. About 52.5% phenotype-positive children and 41% with MaCEs were <10 years old. Only 69% children with early HCM met early screening criteria. Cox regression identified male gender, family history of SCD, and pathogenic variants in MYH7 / MYBPC3 as a predictor of early onset HCM and MaCEs. Conclusion: A third of children not eligible for early screening by current guidelines had phenotype-positive HCM. MYH7 and MYBC3 mutation-positive patients were at highest risk for developing early HCM and experiencing an event or requiring a major intervention. Our findings suggest that younger family members should be considered for early clinical and genetic screening to identify the subset in need of closer monitoring and interventions.